Metabarcoding approach to identify bacterial community profiling related to nosocomial infection and bacterial trafficking-routes in hospital environments - Gimenes de Castro, Bárbara; Mari Fredi, Bruno; dos Santos Bezerra, Rafael; Alcantara, Queren Apuque; Milani Neme, Carlos Eduardo; Mascarelli, Daniele Enriquetto; Carvalho Tahyra, Aline Seiko; dos-Santos, Douglas; Nappi, Camilla Rizzo; Santos de Oliveira, Fernanda; Pereira Freire, Flavia; Ballestero, Giulia; et al. (Taylor & Francis, 2023)
Nosocomial infections (NIs) appear in patients under medical care in the hospital. The surveillance of the bacterial communities employing high-resolution 16S rRNA profiling, known as metabarcoding, represents a reliable method to establish factors that may influence the composition of the bacterial population during NIs. The present study aimed to utilize high-resolution 16S rRNA profiling to identify high bacterial diversity by analyzing 11 inside and 10 outside environments from the General Hospital of Ribeirão Preto Medical School, Brazil. Our results identified a high bacterial diversity, and among these, the most abundant bacterial genera linked to NIs were Cutibacterium, Streptococcus, Staphylococcus, and Corynebacterium. A Acinetobacter was detected in cafeterias, bus stops, and adult and pediatric intensive care units (ICUs). Data suggest an association between transport and alimentation areas proximal to the hospital ICU environment. Interestingly, the correlation and clusterization analysis showed the potential of the external areas to directly influence the ICU pediatric department microbial community, including the outpatient’s clinic, visitor halls, patient reception, and the closest cafeterias. Our results demonstrate that high-resolution 16S rRNA profiling is a robust and reliable tool for bacterial genomic surveillance. In addition, the metabarcoding approach might help elaborate decontamination policies, and consequently reduce NIs.
Keywords: bacterial trafficking-routes; hospital environment; metabarcoding; microbiome; nosocomial infections